Design and Implementation of an Automated Prepaid Water Meter: Case Study of National Water and Sewerage Corporation (NWSC). - Akankwasa, John Bosco (Kabale University, 2023)
The water billing systems currently available in the Ugandan market still incurs costs of reconnection in case of a disconnection, when a client clears the arrears. For example, if a client does not pay in time, a utility officer moves to the point where the water meter is located and disconnects the client to stop having access to water. The same applies to reconnection when a customer clears. This research seeks to solve inconveniences by automating the system. If a customer uses up their credit, then water flow should be stopped instantly. Likewise, if a customer pays the bills, they should access the water instantly. In this way, costs involved in disconnection and reconnection are minimised.